Face mask utilization and associated factors in combating COVID-19 pandemic among government employee in Akaki district administration offices, Oromia, Ethiopia, 2022 - Teka Geferso, Amenti; Desalegn Buta, Derese; Sheikh Said, Adam; Merga Duguma, Geleta (Journal of Community Medicine and Health Solutions, 2022)
Background: The novel coronavirus is a rapidly spreading respiratory disease that has been declared a pandemic by the World Health Organization (WHO) and a global public health emergency. The use of face masks has been recommended by the WHO and the Centers for Disease Control (CDC) as a standard prevention method for transmission of COVID-19. Objective: The objective of this study is to determine face mask utilization and associated factors in combating the COVID-19 pandemic among government employees in Akaki district administration offices in Akaki District, Oromia, Ethiopia, 2022 Methods: A quantitative cross-sectional study was conducted from December 1, 2021, to February 15, 2022, on 385 government employees working in Akaki district administration offices. After obtaining consent from the study participants, data were collected using pretested, self-administered, and standardized questionnaires adapted from other studies. After the data was collected, it was entered into Epi info version 7.2.6, cleaned, and analyzed using SPSS version 26. A logistic regression model was computed to measure the association between the predictor and outcome variables. A p - value of.05 with a 95% CI was used as the cut-off point to declare the level of statistical significance. Results: The study showed that the magnitude of good practice for facemask utilization was 213 (53.5%) (95% CI: 1.50, 1.60) for preventing COVID-19. In the multivariate logistic regression analysis, the odds of using face masks among male employees (AOR = 0.275; 95% CI: 0.137, 0.555), employees aged 20-29 (AOR = 0.17; 95% CI: 0.065, 0.481 ), employees aged 30-39 (AOR = 0.260, 95% CI: 0.109, 0.623), employees of less than five family size (AOR = 0.549, 95% CI: 0.303, 0.995), work experience at 6-12 (AOR = 0, 32, 95 CI: 0.120, 0.450), poor knowledge about face mask use (AOR = 0.504, 95% CI: 0.302, 0.844), and employees with a negative attitude (AOR = 0.430, 95% CI: 0.256, 0.721) were factors significantly associated with face mask utilization. Conclusion: The magnitude of facemask utilization was low (53.5%) compared to other studies. The results of the study showed that age, sex, household family size, work experience, poor knowledge, and the negative attitude of employees toward facemask utilization were among the factors significantly associated with facemask utilization.